When merchandise crowds the aisle and carts crowd the shopper: Joint effects on sales - Mathias C. Streicher (PLoS ONE, 2026)
This research examines how fixture-induced spatial crowding suppresses in-store purchasing and how shopping aids—particularly carts—amplify this effect by expanding users’ peripersonal space and diminishing perceived control. In doing so, it addresses a central trade-off in retail design: while secondary in-aisle fixtures can increase incremental category-level exposure and sales, they simultaneously constrain shoppers’ effective space, leaving the net effect on overall aisle-level purchasing unclear. Across three studies—a 12-week scanner-based field experiment, a behavioral-tracking field experiment, and a scenario-based laboratory experiment—supported by an additional pilot, we provide causal, in-store evidence that fixture-induced spatial crowding reduces purchase behavior, lowering both in-aisle activity and sales. In one field experiment, removing mid-aisle fixtures increased sales despite reduced displayed merchandise. These effects are unlikely to be explained by differences in human crowding, assortment, or promotions. We further demonstrate that the “effective” space a shopper experiences is determined by the retail layout and the shopper’s physical footprint. Shopping aids, especially carts, expand peripersonal space and heighten sensitivity to spatial constraints, reducing perceived control. A moderated-mediation analysis shows that perceived control mediates the effects of spatial crowding on purchasing, with stronger indirect effects for cart (vs. basket) users. The results have clear implications for fixture planning by challenging the widespread assumption that maximizing the use of in-aisle fixtures supports sales at the aggregate level.